Diagnostika stavu tlumiče za jízdy vozidla - Vaněk, Vojtěch (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2021)
Diplomová páce se zabývá analýzou vlivu opotřebení tlumiče na jízdní dynamiku vozidla. Dále byl vytvořen čtvrtinový model automobilu v softwaru Simulink, kde byl vytvořen postup pro vyhodnocování stavu tlumiče za jízdy vozidla. Tento postup byl následně validován na reálně naměřených datech z automobilu Hummer H3.

The diploma thesis deals with the analysis of the effects of shock absorber wear on the driving dynamics of the vehicle. Furthermore, a quarter model of the car was created in the Simulink software, where a procedure for evaluating the condition of the shock absorber while driving the vehicle was created. This procedure was subsequently validated on real measured data from the Hummer H3 car.
On-road Diagnostic of Vehicle Damper
Keywords: Matlab; Simulink; tlumič; opotřebení; diagnostika za jízdy; čtvrtinový model automobilu; Matlab; Simulink; damper; wear; on-road diagnostic; quarter car model